Analisis Volatilitas Harga Komoditas Pangan Strategis Di Provinsi Kalimantan Barat (Studi Kasus Pasar Flamboyan Pontianak) - Imelda, Ryafini Nurmapika, Nurliza, (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2018)
This study examines the strategic comoditas price movements of food and food price volatility of strategic comoditas include sugar, eggs, cooking oil, onion and chilli major upset in the Market Famboyan Pontianak. Quantitative analysis and modeling methods Autoregressive Integrated Moving Average (ARMA), evaluation models korelogram ACF and PACF and strategic analysis of commodity price volatility sugar, eggs, cooking oil, onion and chilli furious with Heteroscedasticity Conditional Autoregressive models (ARCH). Here are the results the development of strategic commodity price red chili, onion, cooking oil, sugar and eggs in the last 5 years ie in 2010 and 2014 showed that certain strategic commodity prices are highly volatile. Weekly food commodity prices in the market positioned Flamboyan Pontianak to commodity sugar, eggs, cooking oil, onion and chilli major upset occurred volatile. It is evident that since the reform of commodity prices weekly positioned in Pontianak Flamboyan market so volatile commodity prices occurs. Even the prices of strategic commodities sugar and red chili, volatilasnya improvement tends to be sustained. Factors affecting price volatility in commodity markets staregis flamboyant pontianak the previous period and the volatility of the price of a variant of the previous period. So it can be interpreted if the prices of strategic commodities today are the price and the residual value of the price variance is relatively large, then the level of strategic commodity prices tomorrow will tend to be large.Keywords: commodity prices, price volatility, arma model, arch model